THE INSTITUTIONALISATION OF MACRO ECONOMIC MEASUREMENT IN INDONESIA BEFORE THE 1980s - Pierre van der Eng (Masyarakat Indonesia, 2013)
Macro-economic measurement goes back to the seventeenth century and becamecommon practice in Western countries since the late-nineteenth century. Since then, thecomposition of some of the largest economies in Asia, particularly India and Japan,was also probed. And since the 1940s government agencies in many Asian countrieshad responsibility for the development and implementation of consistent nationalaccounting practices to assist the planning of economic development. While thiswas in principle also the case in Indonesia, it took into the 1970s before consistentprocesses of macro- economic measurement were put in place that facilitated theanalysis of long-term economic growth. The paper asks why this was the case. It findsthat institutional discontinuities and limited resources prevented the establishment ofconsistent and well-defined national accounting practices until well into the 1970s.Keywords: National accounts, Economic growth, Macro-economic measurement